2021
DOI: 10.3389/fcvm.2021.694711
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Anticancer Therapy-Mediated Vascular Toxicity and New Horizons in Therapeutic Strategies

Abstract: Vascular toxicity is a frequent adverse effect of current anticancer chemotherapies and often results from endothelial dysfunction. Vascular endothelial growth factor inhibitors (VEGFi), anthracyclines, plant alkaloids, alkylating agents, antimetabolites, and radiation therapy evoke vascular toxicity. These anticancer treatments not only affect tumor vascularization in a beneficial manner, they also damage ECs in the heart. Cardiac ECs have a vital role in cardiovascular functions including hemostasis, inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 106 publications
(123 reference statements)
0
11
0
Order By: Relevance
“…Chemotherapy usually induces cardiotoxicity and increases CVD risk ( 27 ). In addition, drugs for CRC usually lead to higher CVD risk than the general population, particularly in the first few years of treatment ( 28 ). However, our analysis indicated that the risks of CVD were significantly lower among patients with CRC who were treated with chemotherapy than those were not.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy usually induces cardiotoxicity and increases CVD risk ( 27 ). In addition, drugs for CRC usually lead to higher CVD risk than the general population, particularly in the first few years of treatment ( 28 ). However, our analysis indicated that the risks of CVD were significantly lower among patients with CRC who were treated with chemotherapy than those were not.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological or genetic inhibition of VEGF, and other key angiogenic signaling pathways accelerate the transition from adaptive cardiac remodeling to HF (60), while anti-angiogenic therapy beneficial to cancer (e.g., metastatic colon cancer, non-small cell lung cancer, breast cancer). However, cancer cells develop adaptive resistance to the antiangiogenic therapy as well as severe cardiotoxicity, leading to development of ischemic CVD and HF (61). Thus, angiogenesis delineates an auspicious substrate for both cancer and HF.…”
Section: Angiogenesismentioning
confidence: 99%
“…On the other hand, vascular toxicity and dysfunction are frequent adverse effects of the currently applied anti-cancer therapy. New predictive and therapeutic strategies are strongly recommended for comprehensive secondary care considering the predictive approach, an aggressive antithrombotic treatment, and cost-effective protection tailored to the personalized patient profile [177,178]. To this end, phytochemicals have been demonstrated as being safe and potentially highly effective in protecting against non-physiologic inflammation, endothelial dysfunction, and cancer-associated stroke [19,[179][180][181].…”
Section: Cancer-associated Thrombosismentioning
confidence: 99%